China's slowdown - Barry Eichengreen (KDI Journal of Economic Policy, 2024)
This paper evaluates explanations for China's growth slowdown. The natural tendency for rapidly growing economies to slow down is a major factor, along with problems bequeathed by unbalanced growth, including a declining ICOR, slowing total factor productivity growth, and rising indebtedness. A number of other mechanisms are of lesser importance: demographics, President Xi's centralization of political power and anti-corruption campaign, and U.S. export controls. Sustaining growth in the longer term will require China to step away from investment, debt and export-fueled growth in favor of a balanced growth model with household consumption playing a larger role. Doing so will require hardening of the budget constraints of regional and local governments and restructuring of the nonperforming debts of property and construction companies.
Keywords: E02; O10; O11; 330; China; Growth Slowdowns; Economic Growth; Debt